1999
DOI: 10.1164/ajrccm.159.6.9805083
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytical Virus–induced Chemokine Expression in the Lower Airways

Abstract: Characterization of chemokine expression patterns in virus-infected epithelial cells provides important clues to the pathophysiology of such infections. The aim of this study was to determine the chemokine response pattern of respiratory epithelium when infected with respiratory syncytial virus (RSV). Macrophage inflammatory protein-1-alpha (MIP-1-alpha), interleukin-8 (IL-8), and RANTES concentrations were measured from RSV-infected HEp-2, MRC-5, and WI-38 cell culture supernatants daily following infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
199
1
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(211 citation statements)
references
References 32 publications
7
199
1
4
Order By: Relevance
“…Eosinophil recruitment and degranulation in lung tissue has been observed in response to RSV infection in humans; [2][3][4]35,36 however, the contributions of this cell to disease and innate immunity have not been clearly defined. We demonstrate here that an airway eosinophilia present constitutively in hypereosinophilic (IL-5 Tg) mice or introduced by transfer of eosinophils directly to the lungs, results in the accelerated clearance of RSV virions and reduction in associated airway dysfunction, including mucus hypersecretion and AHR.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophil recruitment and degranulation in lung tissue has been observed in response to RSV infection in humans; [2][3][4]35,36 however, the contributions of this cell to disease and innate immunity have not been clearly defined. We demonstrate here that an airway eosinophilia present constitutively in hypereosinophilic (IL-5 Tg) mice or introduced by transfer of eosinophils directly to the lungs, results in the accelerated clearance of RSV virions and reduction in associated airway dysfunction, including mucus hypersecretion and AHR.…”
Section: Discussionmentioning
confidence: 99%
“…[15,52,53,58,95,99], which contribute to inflammation by recruiting neutrophils, macrophages and lymphocytes to the airways. Although less well studied, BRSV infection induces a similar up-regulation of pro-inflammatory chemokines and cytokines in the bovine lung.…”
Section: Pathogenesis Of Brsvmentioning
confidence: 99%
“…Nevertheless, the virokinin did not have any direct chemoattractant proprieties on inflammatory cells, in vitro [153]. The chemokines RANTES (CCL5) and MIP-1α (CCL3) are potent attractants for human eosinophils and there is a correlation between levels of MIP-1α and eosinophil cationic protein in the lower airways of infants with severe HRSV disease [58]. However, there were no significant differences in mRNA for either RANTES or MIP-1α in the lungs of calves infected with the F mutant viruses, suggesting that these chemokines may not be involved in eosinophil recruitment in the calf [153].…”
Section: The Role Of the F Protein In The Pathogenesis Of Brsvmentioning
confidence: 99%
“…Therefore, one can imagine that the chemokine profile that follows a particular stimulus will dictate the subsequent inflammatory response. In vitro, RSV infection of human airway epithelial cells has shown that a number of chemokines can be induced, including RANTES, macrophage-inflammatory protein (MIP) 1␣, MIP-1␤, monocyte-derived chemokine; I-309; Exodus; Fractlkine; IL-8; Gro-␣, -␤, and -␥; epithelial neutrophilactivating protein 78; and IFN-inducible T cell ␣ chemoattractant (11)(12)(13)(14). In vivo analyses of sputum samples from infants with RSV show elevated levels of IL-8 (15,16), a CXC chemokine capable of binding CXCR1 and CXCR2 (17).…”
Section: R Espiratory Syncytial Virus (Rsv)mentioning
confidence: 99%